EDUKASI PENGGUNAAN OBAT YANG BAIK DAN BENAR SAAT PUASA - Rissa, Mexsi Mutia (LPPM Akademi Manajemen Administrasi Yogyakarta, 2024)
Indonesia is a country with a majority Muslim population, constituting 87.18% of the total. The Islamic community observes fasting during the month of Ramadan, leading to a change in eating patterns. Similarly, the timing of medication consumption needs to be adjusted. For medications that should be taken every 6 or 8 hours, their use must be adapted to ensure that the patient's treatment is not disrupted, allowing the patient to continue observing fasting rituals. The purpose of this community service is to educate the public about the proper use of medications during fasting. This community service program was attended by 48 individuals from Pokoh I Hamlet, Dlingo, Dlingo, Bantul. The methods employed in this service include direct and indirect approaches using leaflets and posters. The results of this community service include the community being exposed to accurate information regarding the proper use of medications, thus expecting an increase in public knowledge. The conclusion drawn from this activity is that the residents of Pokoh I Hamlet, Dlingo, Dlingo, Bantul, are knowledgeable about how to use medications correctly during fasting.